2022
DOI: 10.1038/s41467-022-33111-4
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the potential of noncanonical amino acid biosynthesis to create cells with precision tyrosine sulfation

Abstract: Despite the great promise of genetic code expansion technology to modulate structures and functions of proteins, external addition of ncAAs is required in most cases and it often limits the utility of genetic code expansion technology, especially to noncanonical amino acids (ncAAs) with poor membrane internalization. Here, we report the creation of autonomous cells, both prokaryotic and eukaryotic, with the ability to biosynthesize and genetically encode sulfotyrosine (sTyr), an important protein post-translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…We reasoned this low efficiency was due to low bioavailability of the nhpSer amino acid given that charged amino acids do not readily traverse cell membranes. Indeed, GCE systems for pSer and pThr incorporation (as well as sulfo-tyrosine) overcame this issue of low target amino acid bioavailability by leveraging biosynthetic pathways that produce high intracellular amino acid concentrations, ,,,, and so we sought to do the same for nhpSer.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned this low efficiency was due to low bioavailability of the nhpSer amino acid given that charged amino acids do not readily traverse cell membranes. Indeed, GCE systems for pSer and pThr incorporation (as well as sulfo-tyrosine) overcame this issue of low target amino acid bioavailability by leveraging biosynthetic pathways that produce high intracellular amino acid concentrations, ,,,, and so we sought to do the same for nhpSer.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that sTyr73 likely contributed more to the binding of HCII's N‐terminal domain to its glycosoaminoglycan binding domain, and the sTyr60 could be more important for thrombin recruitment. A recent report on in situ biosynthesis of sTyr further streamline the GCE approach [156] …”
Section: Sulfotyrosine (Styr)mentioning
confidence: 99%
“…Start‐of‐art genome editing technology also provides more options to conveniently generate engineered organisms containing stop codons in open reading frames through base‐editing technology [61] or the CRISPR‐Cas9 system [43] . The production of phosphor‐threonine, [17c] 5‐hydroxytryptophan, [62] DOPA [63] and sulfotyrosine [64] by coupling biosynthesis pathways with genetic coding has confirmed the feasibility of this approach, which does not require the addition of chemically synthesized CTM amino acids. It would be highly desirable to obtain a method to biosynthesize acylated lysine analogues in eukaryotes, in particular acetyllysine, which would bring the first‐step in the breakthrough to explore the biological or evolutional consequences of PTM versus CTM.…”
Section: Future Directionsmentioning
confidence: 99%